Phase 1, randomized, parallel-group, double-blind, placebo-controlled trial to evaluate the effects of erenumab (AMG 334) and concomitant sumatriptan on blood pressure in healthy volunteers - de Hoon, Jan; Van Hecken, Anne; Vandermeulen, Corinne; Herbots, Marissa; Kubo, Yumi; Lee, Ed; Eisele, Osa; Vargas, Gabriel; Gabriel, Kristin (Cephalalgia, 2019)
Objectives The aim of this study was to assess the effects of concomitant administration of erenumab and sumatriptan on resting blood pressure, pharmacokinetics, safety, and tolerability in healthy subjects. Methods In this phase 1, parallel-group, one-way crossover, double-blind, placebo-controlled study, healthy adult subjects were randomized (1:2) to receive either intravenous placebo and subcutaneous sumatriptan 12 mg (i.e. two 6-mg injections separated by 1 hour) or intravenous erenumab 140 mg and subcutaneous sumatriptan 12 mg. Blood pressure was measured pre-dose and at prespecified times post-dose. The primary endpoint was individual time-weighted averages of mean arterial pressure, measured from 0 hours to 2.5 hours after the first dose of sumatriptan. Pharmacokinetic parameters for sumatriptan were evaluated by calculating geometric mean ratios (erenumab and sumatriptan/placebo and sumatriptan). Adverse events and anti-erenumab antibodies were also evaluated. Results A total of 34 subjects were randomized and included in the analysis. Least squares mean (standard error) time-weighted averages of mean arterial pressure were 87.4 (1.0) mmHg for the placebo and sumatriptan group and 87.4 (1.2) mmHg for the erenumab and sumatriptan group. Mean difference in mean arterial pressure between groups was −0.04 mmHg (90% confidence interval: −2.2, 2.1). Geometric mean ratio estimates for maximum plasma concentration of sumatriptan was 0.95 (90% confidence interval: 0.82, 1.09), area under the plasma concentration–time curve (AUC) from time 0 to 6 hours was 0.98 (90% confidence interval: 0.93, 1.03), and AUC from time 0 to infinity was 1.00 (90% confidence interval: 0.96, 1.05). No clinically relevant safety findings for co-administration of sumatriptan and erenumab were identified. Conclusion Co-administration of erenumab and sumatriptan had no additional effect on resting blood pressure or on pharmacokinetics of sumatriptan. Trial registration: ClinicalTrials.gov, NCT02741310.